A facile preparation method and proof of cycle-stability of carbon-coated metal oxide and disulfide battery materials - Guo, Peng; Singer, Lennart; Zhao, Zhiyong; Kukułka, Wojciech; Sebastian, Finn; Mijowska, Ewa; Zharnikov, Michael; Comba, Peter; Klingeler, Rüdiger (Electrochimica acta, 2023)
Constructing composites of metal oxides and disulfides with carbonaceous materials is considered a useful approach to improve their lithium-ion storage performance. However, complicated synthesis processes and high-cost carbonaceous materials usually used hinder the commercialization of such composites. Here, as an example, carbon-coated tungsten oxides and disulfides are prepared using a facile and simple method on the basis of two kinds of low-cost carbon sources (CTAB and PVP). Following our postulated synthesis route, a variety of carbon-coated WOx, WS2, as well as mixed-phase WOx-WS2 is presented. The CTAB-assisted WOx/C (c-WOx/C), WS2/C (c-WS2/C), and mixed-phase (c-WOx/C-WS2/C) electrodes exhibit outstanding capacity retention of 74%, 99%, and 95%, respectively, which still have 420 mAh g−1, 460 mAh g−1, and 525 mAh g−1 capacity left after 200 cycles at 100 mA g−1. Particularly, the c-WS2/C electrode exhibits superior long-term cycle stability of 97% retention after 500 cycles. Similarly, the PVP-assisted WS2/C (p-WS2/C) electrode displays a capacity retention of 80% after 500 cycles. This work provides an easy and versatile route to fabricate carbon-coated tungsten oxides and disulfides with compelling battery performance and can be easily implemented for other metal oxides and disulfides.
Online verfügbar 12. Mai 2023, Artikelversion 16. Mai 2023
Gesehen am 28.06.2023